Internment Refugee Camps Historical and Contemporary Perspectives - Anderl, Gabriele; Erker, Linda; Reinprecht, Christoph (Histoire, 2022)
How did and does the fate of refugees unfold in internment camps? The contributors to this book facilitate an extensive engagement with the organized, state led, and forced placement of refugees in the past and present. They show the parallels and differences between the practices and types of internment in different countries - while considering the specific historical contexts. Moreover, they highlight the nexus of relationships and agencies which constitute the camps in question as transitory spaces. The contributions consist of analyses of local phenomena or case studies as well as comparative engagements from an international and/or historical perspective.